PENGARUH PENDAMPINGAN DAN BANTUAN AKSES MODAL TERHADAP PENGEMBANGAN USAHA PENGOLAHAN IKAN ASIN DI KELURAHAN HAJORAN KABUPATEN TAPANULI TENGAH - Friska Gebriella Simanjuntak; Risna Uli Sihombing; Sari Mutiara Aritonang; Devolina Lumban Batu; Sri Ulina Wesly Hutagalung (LPPM Universitas HKBP Nommensen, 2022)
This study aims to determine the Effect of Assistance and Access to Capital on the Development of Salted Fish Processing Business in Hajoran Village, Central Tapanuli Regency, using a quantitative approach. The object of research is the Salted Fish Business Processing Society in Hajora Village, totaling 97 people, using primary and secondary data through a Likert scale questionnaire. The research data is processed through validity test, reliability test, multiple regression and hypothesis testing through partial test and simultaneous test. Based on the results of the validity and reliability tests, the variables of Assistance (X1), Access to Capital (X2) and Business Development (Y) can be concluded as valid and reliable based on the testing criteria of rcount > rtable and cronbach alpha > 0.6 of all indicators for each variable. Based on the ttable testing criteria, the resulting tcount value for the Development variable (X1) = 2.667 > ttable (α = 0.05/2; n-k-1) = 1.985. It means that the Assistance variable (X1) has a positive effect on the Business Development variable. Based on the ttable test criteria, the resulting tcount value for the Capital Access variable (X2) = 2.610 > ttable (α = 0.05/2; n-k-1) = 1.985. This means that the variable Access to Capital (X2) has a positive effect on Business Development. Based on Table 4.17, the Fcount value is 13.528 > Ftable (α = k; n-k) = 3.12 with F sig. 0.000 where F sig. 0.000 <0.05 then H0 is rejected. It can be interpreted that Assistance (X1) and Access to Capital (X2) have a positive and significant simultaneous effect on Business Development Decisions (Y).